Designer clown fishes: Unraveling the ambiguities - Anikuttan, Kuttan Kuravamparambu; Rameshkumar, Palsamy; Nazar, Abdul Khudus; Jayakumar, Rengarajan; Tamilmani, Govindan; Sakthivel, Mohammed; Sankar, Murugesan; Bavithra, Rajendran; Johnson, Belevendran; Krishnaveni, Nataraj; Mercy, Augustin Angela; Moulitharan, Nallathambi; et al. (Frontiers in Marine Science, 2022)
The global marine ornamental fish trade is dominated by wild collected fishes, and the contribution from hatchery production is less than 10% of the total. Hatchery production is considered to be the only long-term sustainable option to reduce the fishing pressure on the wild population and also to safeguard the delicate coral reef ecosystem, which houses most of the marine ornamental species. Among the hatchery-produced fishes that are being traded, clown fishes form a dominant group, and a recent addition to this list is the designer clown fishes, which are costlier than other clown fishes due to their rare and attractive color patterns. However, ambiguities about designer clown fish such as its production (wild caught, captive bred, or genetically modified) and taxonomic identity still exist among the general public and hobbyists, as scientific reports on these aspects have not yet been published, even though few aquaculture companies display the photos of designer clown fishes in their websites. The common names for designer clown fishes (such as Platinum, Picasso, and snowflake) have been given by the aquaculture companies/traders solely based on the color patterns or designs on the fish body. The paper describes in detail the production of designer clown fish through captive breeding, followed by elucidating the taxonomic identity of two easily distinguishable designer clown fishes, viz., Picasso and Platinum. Both classical taxonomic tools and molecular methods were employed to elucidate the taxonomic identity. The morpho-merisitic characteristics of Picasso and Platinum were similar to those of Amphiprion percula. The partial cytochrome c-oxidase subunit I (COI) sequences of Picasso and Platinum clown fishes were submitted to the National Center for Biotechnology Information (NCBI) GenBank with accession numbers MT947238 and MT947239, respectively, which had maximum similarity to sequences of A. percula already deposited in the NCBI GenBank. The designer clown fishes exhibited protandrous hermaphroditism with monogamous mating behavior. Their egg incubation period ranged from 7 to 8 days, and the larval rearing was carried out with live feeds such as rotifers and Artemia under the greenwater technique using microalgae, Nannochloropsis oculata. This paper can thus unravel the ambiguities related to the production of designer clown fishes as well as their taxonomy.